IMPROVING THE URBAN ROAD IMPROVEMENT SYSTEM AND IMPROVING THE LANDSCAPE (International conference on multidisciplinary science, 2023)
The traffic service system, together with tools and design, constitutes a complex of facilities and facilities that allow to improve the road, that is, to ensure the normal living conditions of people using the roads and to ensure the functional capabilities of transport.